(Invited) Deep Silicon Etching - Increasingly Relevant >20 Years on!. (28th July 2016) - Thomas, Dave; Muggeridge, Matthew; Hopkins, Janet; Launay, Nicolas; Ashraf, Huma; Barrass, Tony
Abstract : In the early 1990's researchers at the Robert Bosch facility in Stuttgart invented a novel method of etching very deep features into silicon. This led to a patent being granted in 1994. Originally intended as a method of fabricating devices for the then emerging automotive MEMS sector, its use has since diversified to cover virtually all other MEMS markets. Most recently the use of the Bosch Process has expanded into through silicon via (TSV) etching in 3D packaging applications. This paper describes what is possible today using the Bosch process and will consider future applications and uses. The diversity of the approach is illustrated through various examples including cavities etched at high rates, features with aspect ratios of 90:1, profile tilt to ±0.15°, TSVs for wafer stacking and the increasing demand for more precise control including end-point detection down to 0.05% open area.